Building Social Capital: A Study of the Online Disability Community - Huang, Jin; Guo, Baorong (Disability Studies Quarterly, 2005)
There are numerous studies about the relationship between technological aspects of the Internet and disability. However, little is known about the social impact of the Internet on the disability community. Using the theory of social capital, this study aims to understand social aspects of the Internet, specifically its impact on the network building of people with disabilities. Based on survey data from a sample of 122 individuals with disabilities across China, the current study explores the characteristics of social capital in the online disability community and effects of Internet use on building social capital. The findings suggest that the online disability community has high levels of social capital and that greater involvement in online activities can generate higher levels of social capital for people with disabilities.